2004
DOI: 10.1007/s00221-003-1811-z
|View full text |Cite
|
Sign up to set email alerts
|

Postural adjustments due to external perturbations during sitting in 1-month-old infants: evidence for the innate origin of direction specificity

Abstract: The aim of the study was to examine whether infants, at an age when they have no or little experience in sitting, can produce direction specific postural adjustments, i.e. synergies of muscle activity on the ventral side of the body during backward sway and on the dorsal side during forward sway. In addition, we addressed the question whether postural adjustments at this young age are restricted to single muscle responses or consist of a variable repertoire of muscle activation patterns including one during wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 21 publications
0
26
0
1
Order By: Relevance
“…The basic level of control deals with the directional specificity of the adjustments: when the body sways forward, primarily the dorsal muscles are recruited; when the body sways backward, primarily the ventral muscles are activated. 89 A study by Hedberg et al 90 indicated that 1-month-old infants have direction-specific adjustments, which suggests that the basic level of postural control has an innate origin. Young infants show a variable repertoire of direction-specific adjustments from which, from the age of 4 months onward, they learn to select by means of active trial and error the adjustment that fits the situation best.…”
Section: Early Phases Of Motor Developmentmentioning
confidence: 98%
“…The basic level of control deals with the directional specificity of the adjustments: when the body sways forward, primarily the dorsal muscles are recruited; when the body sways backward, primarily the ventral muscles are activated. 89 A study by Hedberg et al 90 indicated that 1-month-old infants have direction-specific adjustments, which suggests that the basic level of postural control has an innate origin. Young infants show a variable repertoire of direction-specific adjustments from which, from the age of 4 months onward, they learn to select by means of active trial and error the adjustment that fits the situation best.…”
Section: Early Phases Of Motor Developmentmentioning
confidence: 98%
“…Moreover, such left-right differences found in object oriented movements could then be attributed to further development of neural control as opposed to organismic constraints such as genetics. Such rapid emergence has been noted between reaching without grasping to reaching with grasping (Wimmers, Savelsbergh, Beek, & Hopkins, 1998) and with early postural control (Hedberg, Forssberg, & Hadders-Algra, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…All of these studies have considered the trunk as a single segment. They have dealt with the lack of trunk control in their subjects by using semireclined and supported seating (Bertenthal et al 1997;van der Fits et al 1999a, 199b;Woollacott et al 1987), propping on arms (Cignetti et al 2011;Harbourne and Stergiou 2003), or allowing the infant's spine to collapse and/or holding the infant up from the chest and releasing the support (Harbourne 1993;Harbourne and Stergiou 2003) just prior to surface perturbation (Hedberg et al 2004(Hedberg et al , 2005. None of these methods has allowed evaluation of, or offered control for, variable contributions of different trunk segments to postural control, and none has addressed the question of how infants acquire a vertical sitting position.…”
mentioning
confidence: 97%